Investigating bacteroidetes gliding motility - Kjaer, A (2022)
Bacteroidetes gliding motility is a type of surface motility in which rod-shaped bacteria move up to 2 µm s in a corkscrewing motion. Flavobacterium johnsoniae is the primary model organism for the study of Bacteroidetes gliding. SprB is the main adhesin in this organism and moves in a helix along the cell surface. This movement is guided by an underlying track that is anchored to the inner leaflet of the outer membrane. The essential gliding lipoprotein GldJ, which is helically arranged when visualised in fixed cells, is suggested to form this track. However, direct in vivo imaging of GldJ is yet to be achieved. Two currently outstanding questions about Bacteroidetes gliding motility are 1) how adhesion of SprB to the substratum is controlled so that binding only occurs when moving from the leading to the lagging cell pole and 2) how/if the cell discriminate between the poles. In this thesis, a fusion of the HaloTag domain to SprB enabled labelling of SprB with stable and bright dyes. The movement of SprB could then be visualised using single-particle tracking to reveal the underlying track topology. These tracking data suggest that the underlying track is not a single closed loop currently proposed, but rather a complex and potentially dynamic structure that can form multiple loops and cover most of the cell surface.